Unsteady computational fluid dynamics in front crawl swimming. Issue 7 (19th May 2017) - Samson, Mathias; Bernard, Anthony; Monnet, Tony; Lacouture, Patrick; David, Laurent
Abstract: The development of codes and power calculations currently allows the simulation of increasingly complex flows, especially in the turbulent regime. Swimming research should benefit from these technological advances to try to better understand the dynamic mechanisms involved in swimming. An unsteady Computational Fluid Dynamics (CFD) study is conducted in crawl, in order to analyse the propulsive forces generated by the hand and forearm. The k-ω SST turbulence model and an overset grid method have been used. The main objectives are to analyse the evolution of the hand-forearm propulsive forces and to explain this relative to the arm kinematics parameters. In order to validate our simulation model, the calculated forces and pressures were compared with several other experimental and numerical studies. A good agreement is found between our results and those of other studies. The hand is the segment that generates the most propulsive forces during the aquatic stroke. As the pressure component is the main source of force, the orientation of the hand-forearm in the absolute coordinate system is an important kinematic parameter in the swimming performance. The propulsive forces are biggest when the angles of attack are high. CFD appears as a very valuable tool to better analyze the mechanisms of swimming performance and offers some promising developments, especially for optimizing the performance from a parametric study.